2014
DOI: 10.1007/s00127-014-0905-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of deprivation on suicide mortality in urban and rural Queensland: an ecological analysis

Abstract: The extent to which social deprivation contributes to suicide mortality varies considerably between rural and urban areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Of those factors that were significant for both sexes, it was found that areas with large proportions of tenant household dwellers had higher suicide rates for older persons, especially for older men. These findings are consistent with other studies in most English‐speaking countries, which suggest that housing is one of the most important necessities in people's lives (Burrows and Laflamme, ; Ayala and Navarro, ; Law et al ., ). Those unable to afford a private shelter are more likely to suffer from social disadvantage, have a low income and experience a lack of labour force engagement, all of which are related to a higher risk of suicide in English‐speaking countries (Ayala and Navarro, ; Baum, ).…”
Section: Discussionsupporting
confidence: 93%
“…Of those factors that were significant for both sexes, it was found that areas with large proportions of tenant household dwellers had higher suicide rates for older persons, especially for older men. These findings are consistent with other studies in most English‐speaking countries, which suggest that housing is one of the most important necessities in people's lives (Burrows and Laflamme, ; Ayala and Navarro, ; Law et al ., ). Those unable to afford a private shelter are more likely to suffer from social disadvantage, have a low income and experience a lack of labour force engagement, all of which are related to a higher risk of suicide in English‐speaking countries (Ayala and Navarro, ; Baum, ).…”
Section: Discussionsupporting
confidence: 93%
“…To study how suicide rates vary between rural and urban areas, research studies have often used centralized registries, coroners' reports and death certificates as a basis for investigation. Most studies have been conducted in High Income countries, including six from Australia, [201][202][203][204][205][206] four from the United States, [207][208][209][210] two from Austria, 211,212 three from the UK, [213][214][215] one from Canada 216 and one from New Zealand 217 (Table 5). More recently, a handful of studies have been conducted in LAMIC countries,…”
Section: Urban Vs Rural Settingsmentioning
confidence: 99%
“…230 As before, this research has primarily been conducted in High Income countries, including Denmark, 231 Australia, 232 New Zealand, 233 the UK, 213,[234][235][236][237] United States, 208,238 Canada, 216 Belguim, 230 Austria, 212 Netherlands, 193 Finland, 239 Taiwan, 218,241 Brazil, 242 Slovenia 243 and Japan. 244 Both social fragmentation, 223,230,236,237,243 and deprivation 193,203,230,233,236,239 have been associated with suicide mortality, as well as some evidence of a relationship with income inequality, 239 low social capital (in particular social trust), 193,208,240,244 and low population density. 208,213,230,232 Nonetheless, these relationships have not been uniformly observed, with for example, Chang et al 218 finding that social fragmentation was not strongly or consistently associated with suicide rates in Taiwan.…”
Section: Neighbourhoodsmentioning
confidence: 99%
“…Indigenous and Torres Strait Islander communities have a 20% lower life expectancy than non-Indigenous communities, with higher unemployment rates and lower socioeconomic status. These disparities are exacerbated in rural and particularly remote areas and can impact on later suicide risk 41 …”
mentioning
confidence: 99%
“…These include increased identification of people at risk through screening 30 , increased clinical and telepsychiatry services to assist rural GPs caring for rural people at risk 27 and further research into suicide risk factors, comparisons with other male-dominated occupations. Along with further examination of the incidence of farming suicides, these may provide a more complete picture of the complexities of older male suicide in rural Australia 10,41 . Kennedy et al 13 suggest there needs to be more discussion and research into the impact of suicide on communities, and an understanding of the specific needs of farming communities, both in the local and regional sense.…”
mentioning
confidence: 99%